Art and the Nekyia : a study of the significance of the symbolic descent into Hades in art, myth and ritual - Place, L B (Rhodes University, Faculty of Humanities, Department of Fine Art, 1975)
Art has very littlo to do with the dead. Death alone is the negation of creation, ,while art is a vital force, a deeply instinctive, everlasting, continual revitalisation. Art is life and nature and it lives in the realms of imagination, magic and mystery. Its language is the language of myth, and its aim is Truth. Art is action and reaction and is reached in silence by the artist alone and individually - its climate is solitude and its paths are as devious and labyrinthine as any the soul can follow in search of self-knowledge and the divine. Chap. 1, p. 1.
Keywords: Hell in art; Death in art; Death -- Psychological aspects; Hell in literature